2015
DOI: 10.1371/journal.pone.0144022
|View full text |Cite
|
Sign up to set email alerts
|

Genotypic Diversity within a Single Pseudomonas aeruginosa Strain Commonly Shared by Australian Patients with Cystic Fibrosis

Abstract: In cystic fibrosis (CF), Pseudomonas aeruginosa undergoes intra-strain genotypic and phenotypic diversification while establishing and maintaining chronic lung infections. As the clinical significance of these changes is uncertain, we investigated intra-strain diversity in commonly shared strains from CF patients to determine if specific gene mutations were associated with increased antibiotic resistance and worse clinical outcomes. Two-hundred-and-one P. aeruginosa isolates (163 represented a dominant Austral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
34
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(36 citation statements)
references
References 39 publications
2
34
0
Order By: Relevance
“…Due to the different conditions present in different areas of the respiratory tract, many variants of the same infecting strain may exist and heterogeneity within one population is common in the CF lung [111113]. The heterogeneity manifests both in terms of genetic and physiological diversity and spatial distributions in the airways.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the different conditions present in different areas of the respiratory tract, many variants of the same infecting strain may exist and heterogeneity within one population is common in the CF lung [111113]. The heterogeneity manifests both in terms of genetic and physiological diversity and spatial distributions in the airways.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies on P. aeruginosa strains isolated from CF sputum samples, found significant genomic changes in lasR, including truncation, deletion, frame shifts and SNPs, with many resulting in a loss of function (30,39,40,49,69). Although there can be a high percentage of lasR-deficient isolates collected from patients, studies have also shown differential frequencies of functional and intact lasR alleles within patients (13,70). Considering the importance of lasR-dependent social interactions for the fitness of P. aeruginosa, mutation-frequency of lasR within populations of P. aeruginosa could significantly impact on QS-dependent phenotypes and fitness at the population level (71)(72)(73).…”
Section: Discussionmentioning
confidence: 99%
“…AUST-02 is a prevalent shared strain in CF centres around Australia and is the dominant strain in Queensland infecting approximately 40% of patients infected with P. aeruginosa [10, 14, 15]. A recent surveillance study also described the detection of an AUST-02 strain sub-type in approximately 5% of patients attending a single CF treatment centre in Brisbane (Queensland) [16]. This sub-type could be distinguished from all other AUST-02 strains by a unique mexZ ( mexZ-3, M3) and lasR ( lasR -7, L7) genotype and therefore, was designated M3L7 [16].…”
Section: Introductionmentioning
confidence: 99%
“…A recent surveillance study also described the detection of an AUST-02 strain sub-type in approximately 5% of patients attending a single CF treatment centre in Brisbane (Queensland) [16]. This sub-type could be distinguished from all other AUST-02 strains by a unique mexZ ( mexZ-3, M3) and lasR ( lasR -7, L7) genotype and therefore, was designated M3L7 [16]. The M3L7 sub-type is of particular importance given that, compared to other AUST-02 and P. aeruginosa strains, it is associated with enhanced antibiotic resistance and poorer clinical outcomes (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation